(untitled) (Research, Society and Development, 2023)
This project aims to develop a guide, which through its development will enable small companies that cannot afford IT professionals to have knowledge of how important the security of their business data is. Information security has become essential and critical for any business today. The methodology is based on a bibliographic survey and based on law No. 13,709, of August 14, 2018, General Data Protection Law (LGPD), the types of research techniques used in this article, is exploratory and explanatory. A small semi-structured questionnaire was applied for data collection in the small company located in the city of Redenção do Pará. The survey revealed that it is possible for small businesses to have a secure IT environment, it is important to have information security knowledge and be aware of cyberattacks.